The Role of Saint Augustine, Thomas Aquinas, and Ibn Khaldun in the Philosophy of History - Budi Sujati; Ajid Thohir; Dedi Supriadi; Agus Permana (Gunung Djati Conference Series, 2026)
The philosophy of history is a branch of philosophy that attempts to understand and explain the course of human history through various theoretical approaches. In this context, Saint Augustine, Thomas Aquinas, and Ibn Khaldun played a very important role in shaping the historical thought that has developed to this day. Saint Augustine, with his main work De Civitate Dei, introduced the view of history as a journey towards the kingdom of God, linking theological beliefs with worldly developments. Thomas Aquinas, with his rational and theological approach, developed a theory of history that sought to harmonize Christian teachings with Greek philosophical thought, particularly Aristotle, and explained the role of reason in understanding human history. On the other hand, Ibn Khaldun, as a Muslim thinker, made a major contribution with his theory of historical science in the Muqaddimah, where he viewed history as a dynamic process influenced by social, economic, and cultural factors, and developed the concept of asabiyyah, which explains the relationship between group solidarity and changes in society. These three figures, although from different backgrounds, present a rich and profound view of the dynamics of human history, which informs various perspectives on the roles of religion, reason, and social factors in historical development.